Differences in Chronic Disease Behavioral Indicators by Sexual Orientation and Sex. (January 2016) - Minnis, Alexandra M.; Catellier, Diane; Kent, Charlotte; Ethier, Kathleen A.; Soler, Robin E.; Heirendt, Wendy; Halpern, Michael T.; Rogers, Todd
Abstract : Context: Lesbian, gay, and bisexual (LGB) populations experience significant health inequities in preventive behaviors and chronic disease compared with non-LGB populations. Objectives: To examine differences in physical activity and diet by sexual orientation and sex subgroups and to assess the influences of home and neighborhood environments on these relationships. Design: A population-based survey conducted in 2013-2014. Setting: A stratified, simple, random sample of households in 20 sites in the United States. Participants: A total of 21 322 adult LGB and straight-identified men and women. Outcome Measures: Any leisure-time physical activity in the past month; physical activity 150 min/wk or more; daily frequency of consumption of vegetables, fruit, water, and sugar-sweetened beverages; and the number of meals prepared away from home in the past 7 days. Results: Physical activity and diet varied by sexual orientation and sex; differences persisted after adjusting for sociodemographic factors and household and community environments. Bisexual men reported a higher odds of engaging in frequent physical activity than straight men (odds ratio [OR] = 3.10; 95% confidence interval [CI], 1.57-6.14), as did bisexual women compared with straight women (OR = 1.84; 95% CI, 1.20-2.80). LGB subgroups reported residing in more favorable walking and cycling environments. In contrast, gay men and lesbian and bisexual women reported a less favorable community eating environment (availability, affordability, and quality of fruit and vegetables) and a lower frequency of having fruit or vegetables in the home. Lesbian women reported lower daily vegetable consumption (1.79 vs 2.00 mean times per day; difference = −0.21; 95% CI, −0.03 to −0.38), and gay men reported consumption of more meals prepared away from home (3.17 vs 2.63; difference = 0.53; 95% CI, 0.11-0.95) than straight women and men, respectively. Gay men and lesbian and bisexual women reported a higher odds of sugar-sweetened beverage consumption than straight men and women. Conclusions: Findings highlight opportunities for targeted approaches to promote physical activity and mitigate differences in diet to reduce health inequities. Abstract : This article examines differences in physical activity and diet by sexual orientation and sex subgroups and assesses the influence of home and neighborhood environments on these relationships.